A construção de igualdade de gênero no currículo da educação de adolescentes, jovens e adultos na rede municipal de ensino de Goiânia - Gomes, Maria Antônia de Paula (2016)
This work refers to action research conducted in the field school and participation in the GTE of the Municipal Education Network to rewrite the PPP / EAJA 2017. The purpose of this action research was to include the issues of gender and sexuality in the curriculum of Adolescent, Youth and Adult Education (EAJA) at the field school and Teaching Municipal Network of Goiânia (RME). The survey questioned the curriculum of Adolescent, Youth and Adult Education, their proposals and measures and these are viable to the discussion of gender and sexuality in the school environment of Adolescent, Youth and Adult Education. Initially, remounted to the history of youth and adult education in Brazil and Goiânia’s Municipal Secretary of Education, the identity of the subject of adult education, cultural diversity that characterizes the adult education and discussion of a curriculum to be developed in EAJA, and the debate about a curriculum to be developed in the Adolescent, Youth and Adult Education, considering cultural diversity and the themes of gender and sexuality. The methodology chosen for this research was the action research, qualitative with participant observation in which the researcher sought to integrate into the daily life of Field School, in order to better understand the social interactions and the pedagogical praxis of the subjects. This research technique in education allows the participation of all the involved throughout the process and in the research and intervention decisions. To make a pedagogical practice focused on the dialogue with the various identities that make up the cultural diversity of the EJA was analyzed various official documents such as the National Curriculum Parameters: Transversal themes (BRAZIL, 1998). Report Nº. 11/2000-CNE / CEB, National Curriculum Guidelines for Youth and Adult Education (BRAZIL, 2000), the Law of Directives and Bases of Education (BRAZIL, 2010), and others like National Document Preparation CONFINTEA VI (BRAZIL, 2009) which allow the school to build its curriculum to meet the specific characteristics of their subjects and promoting multiculturalism. This action research contributed to the process, still under construction, a new school culture of respect for cultural diversity, gender and sexuality in school field. Continuing education worked in study groups with the participating teachers about the themes of gender and sexuality with the prospect of drawing up speech and gender equality practice, that is to say, overcoming inequalities between women and men. During the continuing education the participating teachers planned the didactic sequences to work with the students in classroom. The topics of the classes treated in general gender issues, with specificity for domestic violence, family planning, maternity and women and the world of work. It was also worked sexual diversity and corporeality. The result of such training culminated in the development of the educational object structured in two teaching sequences with suggestions of teaching practices for the development of speech and practice of gender equality and sexuality at school. Participation in the GTE that rewrote the curriculum proposal for EAJA at the RME witnessed the inclusion of issues of gender and sexuality in the PPP / EAJA (2017).